Pengaruh Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Kritis Dan Kemampuan Berpikir Kreatif MTs Nurul Hikmah Tinjowan Kab. Simalungun - Sabariyah; Hasratuddin; Isti Rokhiyah (Jurnal Serambi Ilmu, 2024)
The purposes of this study are to examine: (1) Influence critic thingking abilities of students who obtained a model of problem-based learning better than students who received direct instruction model, (2) Influence the creative thinking ability of students who get problem based learning is better than students who received direct instruction, (3) Levels of student activity during problem-based learning process in progress, (4) The pattern of responses of the students in solving problems in each lesson. That analysis was performed with analysis of covariance (ANAKOVA). The main result of this study is the overall student learning with problem-based learning is significantly better in improving critic thingking skills and creative thinking skilsl than students with hands-on teaching. Descriptively also reviewed the answers from the formulation of the problem are: (1) Activities of students in problem-based learning is effective. (2) The pattern of responses of the students are learning using problem-based learning model is better than the students who are learning to use the direct instruction model. Based on the results of the study, the researchers recommend that: (1) problem-based learning in english learning that emphasizes critic thingking skills and creative thinking skills students can be used as an alternative for implementing innovative english learning. (2) Activities of students in problem-based learning is effective. English teachers are expected to create a joyful learning, allowing students to express ideas in their own